Cross-curricular perspectives on English language education: A Qualitative comparative study between Indonesia and Australia - Saputra, Muhammad Ari; Rizky Yolanda; Zelly Putriani (Journal of English and Education (JEE), 2025)
This study compares English language education in Indonesia and Australia, focusing on cross-curricular integration, teacher autonomy, technology use, and the influence of sociopolitical contexts on curriculum design. While both countries aim to enhance English language proficiency, their approaches differ significantly due to contextual factors. In Australia, the decentralized education system promotes teacher autonomy, allowing for innovative, student-centered teaching practices, cross-curricular integration, and frequent use of technology to enhance language learning. In contrast, Indonesia’s centralized education system, heavily influenced by national exam structures, limits the flexibility of teachers and the integration of English across subjects. Despite recent reforms, teachers in Indonesia face challenges in adopting modern pedagogies due to resource constraints and the continued focus on standardized testing. Through a qualitative comparative analysis of policy documents, curriculum standards, and teacher perspectives, this study highlights the importance of localized educational reforms. The findings suggest that fostering teacher autonomy, improving technology access, and reducing exam-driven practices could lead to more effective, cross-curricular English language education in Indonesia. The study also emphasizes the role of sociopolitical factors in shaping curriculum design and calls for greater international collaboration in sharing best practices to enhance English education in both countries.